Study of the effectiveness of additional reductions in cholesterol and homocysteine (SEARCH): characteristics of a randomized trial among 12064 myocardial infarction survivors. - Bowman, L; Armitage, J; Bulbulia, R; Parish, S; Collins, R (2007)
BACKGROUND: Cholesterol lowering with statins reduces the risk of vascular disease, but uncertainty remains as to whether more intensive statin therapy produces worthwhile benefits safely. Blood homocysteine level is an independent marker of vascular risk, but it is unknown whether this association is causal. METHODS AND RESULTS: 12,064 myocardial infarction survivors have been randomized to more versus less intensive cholesterol-lowering treatment using simvastatin 80 mg versus 20 mg daily. Allocation to more intensive treatment has yielded average further low-density lipoprotein cholesterol reductions of 0.5 mmol/L at 2 months and 0.4 mmol/L at 5 years. In addition, using a factorial design, these patients have been randomized to homocysteine lowering with folic acid 2 mg plus vitamin B12 1 mg daily versus matching placebo, yielding an average 3 to 4 mumol/L reduction in homocysteine. After 6 years of median follow-up, the annual overall rate of major vascular events is approximately 3%. Follow-up is scheduled to continue for a median of 7 years. CONCLUSION: SEARCH should provide reliable evidence about the efficacy and safety of prolonged use of more intensive cholesterol-lowering therapy and, separately, of folate-based homocysteine-lowering therapy in a high-risk population.